Advancing Sudbury Exploration with 3D Modelling - D. Richardson (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Presentation Objectives ?Demonstrate the utility of 3D modelling for visualizing exploration data ?Demonstrate the target generation ability of 3D model query methods Exploration Criteria -Example Given the Geology of Sudbury What Are Our Exploration Criteria? (selected examples) ?Geometry ?Trends ?Lithology ?Proximity to Sulphides ?Length and Grade of Anomalous Mineralization ?Distance from Footwall In Addition ?Geophysical Criteria ?Economic Criteria ?Amount of Available Space ? Depth